Acute Febrile Illness Accompanied by 7th and 12th Cranial Nerve Palsy Due to Lyme Disease Following Travel to Rural Ecuador: A Case Report and Mini-Review - Teslin S. Sandstrom; Kumudhavalli Kavanoor Sridhar; Judith Joshi; Ali Aunas; Sheliza Halani; Andrea K. Boggild (Tropical Medicine and Infectious Disease)
The causative agent of Lyme disease, Borrelia burgdorferi, is endemic to Canada, the northeastern United States, northern California, and temperate European regions. It is rarely associated with a travel-related exposure. In this report, we describe a resident of southern Ontario, Canada who developed rash, fever, and cranial nerve VII and XII palsies following a 12 day trip to Ecuador and the Galapagos islands approximately four weeks prior to referral to our center. Comprehensive microbiological work-up was notable for reactive Borrelia burgdorferi serology by modified two-tier testing (MTTT), confirming a diagnosis of Lyme disease. This case highlights important teaching points, including the classic clinical presentation of acute Lyme disease with compatible exposure pre-travel in a Lyme-endemic region of Ontario, initial manifestations during travel following acquisition of arthropod bites in Ecuador, and more severe manifestations post-travel. Given the travel history to a South American country in which Lyme disease is exceedingly uncommon, consideration of infections acquired in Ecuador necessitated a broad differential diagnosis and more comprehensive microbiological testing than would have been required in the absence of tropical travel. Additionally, cranial nerve XII involvement is an uncommon feature of Lyme neuroborreliosis, and therefore warranted consideration of an alternative, non-infectious etiology such as stroke or a mass lesion, both of which were excluded in this patient through neuroimaging.